Biomarker analysis beyond angiogenesis: RAS/RAF mutation status, tumour sidedness, and second-line ramucirumab efficacy in patients with metastatic colorectal carcinoma from RAISE-a global phase III study - Yoshino, T; Portnoy, D C; Obermannová, R; Bodoky, G; Prausová, J; Garcia-Carbonero, R; Ciuleanu, T; García-Alfonso, P; Cohn, A L; Van Cutsem, E; Yamazaki, K; Lonardi, S; et al. (Annals of oncology, 2019)
BACKGROUND: : Second-line treatment with ramucirumab+FOLFIRI improved overall survival (OS) versus placebo+FOLFIRI for patients with metastatic colorectal carcinoma (CRC) [hazard ratio (HR)=0.84, 95% CI 0.73-0.98, P = 0.022]. Post hoc analyses of RAISE patient data examined the association of RAS/RAF mutation status and the anatomical location of the primary CRC tumour (left versus right) with efficacy parameters. PATIENTS AND METHODS: Patient tumour tissue was classified as BRAF mutant, KRAS/NRAS (RAS) mutant, or RAS/BRAF wild-type. Left-CRC was defined as the splenic flexure, descending and sigmoid colon, and rectum; right-CRC included transverse, ascending colon, and cecum. RESULTS: RAS/RAF mutation status was available for 85% of patients (912/1072) and primary tumour location was known for 94.4% of patients (1012/1072). A favourable and comparable ramucirumab treatment effect was observed for patients with RAS mutations (OS HR = 0.86, 95% CI 0.71-1.04) and patients with RAS/BRAF wild-type tumours (OS HR = 0.86, 95% CI 0.64-1.14). Among the 41 patients with BRAF-mutated tumours, the ramucirumab benefit was more notable (OS HR = 0.54, 95% CI 0.25-1.13), although, as with the other genetic sub-group analyses, differences were not statistically significant. Progression-free survival (PFS) data followed the same trend. Treatment-by-mutation status interaction tests (OS P = 0.523, PFS P = 0.655) indicated that the ramucirumab benefit was not statistically different among the mutation sub-groups, although the small sample size of the BRAF group limited the analysis. Addition of ramucirumab to FOLFIRI improved left-CRC median OS by 2.5 month over placebo (HR = 0.81, 95% CI 0.68-0.97); median OS for ramucirumab-treated patients with right-CRC was 1.1 month over placebo (HR = 0.97, 95% CI 0.75-1.26). The treatment-by-sub-group interaction was not statistically significant for tumour sidedness (P = 0.276). CONCLUSIONS: In the RAISE study, the addition of ramucirumab to FOLFIRI improved patient outcomes, regardless of RAS/RAF mutation status, and tumour sidedness. Ramucirumab treatment provided a numerically substantial benefit in BRAF-mutated tumours, although the P-values were not statistically significant. CLINICALTRIALS.GOV NUMBER: NCT01183780.
Keywords: Colorectal Neoplasms; Humans; Ramucirumab; fluoruracil; cetuximab; Leucovorin; Biomarkers, Tumor; kamptothecin; Female; mutace; Aged; ras Proteins; protokoly protinádorové kombinované chemoterapie; Cetuximab; senioři; lidé; humanizované monoklonální protilátky; leukovorin; Proto-Oncogene Proteins c-raf; Neovascularization, Pathologic; nádorové biomarkery; Neoplasm Metastasis; Antibodies, Monoclonal, Humanized; metastázy nádorů; Camptothecin; ženské pohlaví; Follow-Up Studies; kolorektální nádory; Male; prognóza; Antineoplastic Combined Chemotherapy Protocols; Fluorouracil; Ras proteiny; ramucirumab; protoonkogenní proteiny c-raf; míra přežití; Mutation; mužské pohlaví; patologická angiogeneze; Prognosis; následné studie; Survival Rate